Weather Conditions and Daily Commuting - Ignacio Belloc; J. Ignacio Gimenez-Nadal; José Alberto Molina (Institute of Labor Economics (IZA), 2022)
Climate change and global warming are problems that currently affect the daily lives of the world population and, to the extent that climate projections are less than optimistic, understanding how individuals respond to extreme weather conditions is essential for the correct design of public policies. One of the human behaviors that can be most affected by extreme weather conditions is that of personal travel, including commuting, an activity that is done daily by millions of workers worldwide. Within this framework, we estimate the effects of weather conditions on daily commuting and travel choices, by examining daily variations in weather conditions within counties in the US. To that end, we use timeuse diary information from the American Time Use Survey 2003-2019 and daily weather information at the county level for a sample of US workers, finding significant relationships between daily weather conditions, commuting time, and travel choices. Rainy days, high temperatures, and snowfall are associated with a statistically significant lower proportion of commuting time done by public transit and walking, whereas the relationship is found to be positive for the proportion of commuting time by car. With additional analysis, we find that the greatest substitution from greener modes of transport towards the private car is concentrated on days with greater precipitation and higher temperatures. Finally, our results suggest adaptation to higher temperatures in warmer places.
Keywords: R4; J22; 330; weather; commuting; green mobility; workers; American Time Use Survey